Impact of Land-Use Change on Soil Carbon Dynamics in Tropical Peatland, West Kalimantan- Indonesia - Rossie Wiedya Nusantara; Sudarmadji Sudarmadji; Tjut S. Djohan; Eko Haryono (Indonesian Journal of Geography, 2020)
The conversion of tropical peat forest to other land uses can reduce organic carbon (C) and stable C isotope (δ13C) of peat soil. This research aimed at analyzing the soil organic-C and δ13C of peatland with respect to maturity (fibric, hemic and sapric) in five types of peatland use, which included primary peat forest, secondary peat forest, shrubs, oil palm plantations, and cornfield in West Kalimantan. Analysis of peat soil samples includes organic C with Loss in ignition method and δ13C  using an isotope ratio mass spectrometry(IRMS) method. Organic-C at fibric was higher than hemic and sapric, respectively (57.2%, 57.0%, 56.4%), meanwhile, organic-C was the highest on primary peat forest, followed by on secondary peat forest, oil palm plantation, cornfield, and shrubs, respectively 57.1%, 57.0%, 56.4%, 56.0%. The cause of increasing and decreasing organic C and δ13C due to land-use change due to changes in vegetation, burning during tillage, and age of organic matter of peat soil. This condition causes the opening of natural peat ecosystems and changes in anaerobic to aerobic conditions.